2004
DOI: 10.1007/bf03403642
|View full text |Cite
|
Sign up to set email alerts
|

Measured Weights in PEI Adults Reveal Higher Than Expected Obesity Rates

Abstract: Background: The increasing prevalence of obesity and overweight in Canada is a significant health concern. Unfortunately, we know very little about the actual weight status and associated health risks in our population since most surveys use only selfreported body weights and heights and typically do not include a measure of body fat distribution. This paper summarizes the findings of the Prince Edward Island Nutrition Survey. Methods: A random sample of 1,995 adults aged 18-74 were interviewed in their homes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 10 publications
2
14
0
4
Order By: Relevance
“…The inconsistency around obesity prevalence estimates because of self-report for height and weight has recently been investigated (15). Comparing measured data collected in 1995 adults from PEI (one of the 10 Canadian provinces) with self-reported anthropometric data from the 1995 NPHS, MacLellan et al .…”
Section: Current Prevalencementioning
confidence: 99%
“…The inconsistency around obesity prevalence estimates because of self-report for height and weight has recently been investigated (15). Comparing measured data collected in 1995 adults from PEI (one of the 10 Canadian provinces) with self-reported anthropometric data from the 1995 NPHS, MacLellan et al .…”
Section: Current Prevalencementioning
confidence: 99%
“…While there are few studies of obesity in rural North American adults, they consistently report a significant gender difference in obesity prevalence. Women have higher obesity prevalence than men in both Canadian and US studies (Borders et al, 2006;Liebman et al, 2003;MacLellan et al, 2004;Self et al, 2005). This gender difference is less consistently observed in studies of rural children.…”
mentioning
confidence: 97%
“…There is also national-level literature that demonstrates heightened obesity risk for North Americans experiencing socioeconomic deprivation (Alaimo et al, 2001;Gordon-Larsen et al, 2003;Phipps et al, 2006;Willms et al, 2003). However, researchers stress the need for directly measured data at both the national and local levels in order to develop understandings of the global and proximate causes of obesity in the environment (MacLellan et al, 2004;Tremblay, 2004).…”
mentioning
confidence: 99%
“…Without adjustment, these measures could lead to a significant underestimation of the obesity prevalence due to misclassification in BMI category. 16,23 Such misclassification may affect not only the magnitude but also the direction of the predicted relationships between obesity and illhealth, thereby blurring understanding of the association between obesity and disease risk factors, which may ultimately influence public policy decisions. To the best of our knowledge, this is the first study to make use of telephone surveys in developing correction equations to adjust deviations between self-reported and measured height and weight in the Canadian context.…”
Section: Discussionmentioning
confidence: 99%
“…10 Other determinants such as income, education and occupation also have been linked to the discordance between self-reported and actual height and weight measurements. 14,17 A number of studies argue that systematic errors in self-reported height and weight lead to an underestimation of the proportion of overweight or obese people in the general population, 23 which indisputably poses challenges in measuring and monitoring the prevalence and trends of obesity, distorts the classification of individuals with regard to chronic conditions, 8 and ultimately, confounds the association of BMI with mortality. 24 Given that most health surveys collect self-reported data, the idea of adjusting self-reported height and weight has been explored in a handful of empirical studies in the Canadian context.…”
mentioning
confidence: 99%